Beyond Social Capital: Spatial Dynamics of Collective Efficacy for Children - Sampson, Robert J.; Morenoff, Jeffrey D.; Earls, Felton (American Sociological Review, 1999)
We propose a theoretical framework on the structural sources and spatially embedded nature of three mechanisms that produce collective efficacy for children. Using survey data collected in 1995 from 8,782 Chicago residents, we examine variations in intergenerational closure, reciprocal local exchange, and shared expectations for informal social control across 342 neighborhoods. Adjusting for respondents’ attributes, we assess the effects of neighborhood characteristics measured in the 1990 census and the role of spatial interdependence. The results show that residential stability and concentrated affluence, more so than poverty and racial/ethnic composition, predict intergenerational closure and reciprocal exchange. Concentrated disadvantage, by contrast, is associated with sharply lower expectations for shared child control. The importance of spatial dynamics in generating collective efficacy for children is highlighted—proximity to areas high in closure, exchange, and control bestows an advantage above and beyond the structural characteristics of a given neighborhood. Moreover, spatial advantages are much more likely to accrue to white neighborhoods than to black neighborhoods.